Anti-Arthritic, Anti-Lipoxygenase, and Nitric Oxide Production Inhibition Activities of Cucumis Melo Agrestis and Albizia Thompsonii - P. Terse, Pratik; Bhargava, Sushil; Chandavarkar, Sachin (Journal of Neonatal Surgery, 2025)
The increasing prevalence of inflammatory diseases, such as rheumatoid arthritis and osteoarthritis, has prompted the search for alternative treatments, particularly from natural sources. This study explores the anti-arthritic, anti-lipoxygenase, and nitric oxide (NO) production inhibition activities of Cucumis melo agrestis and Albizia thompsonii, two medicinal plants native to India. These plants have been traditionally used for their anti-inflammatory, antioxidant, and analgesic properties. The extracts of both plants were evaluated for their ability to inhibit protein denaturation, a key mechanism in rheumatoid arthritis (RA), as well as their effects on lipoxygenase (LOX) activity and NO production in macrophages. The results demonstrated that both Cucumis melo agrestis and Albizia thompsonii exhibited significant anti-arthritic effects by inhibiting BSA denaturation, with IC50 values comparable to that of diclofenac sodium. Furthermore, the extracts showed notable inhibitory effects on 15-lipoxygenase activity and reduced NO production in a concentration-dependent manner. These findings suggest that both plants possess strong anti-inflammatory potential and may offer a promising alternative to conventional anti-inflammatory drugs, potentially reducing the reliance on synthetic medications and their associated side effects.